I married a "thinker" - Rolston, Jane, author (Colorado State University. Libraries, 1995)
Recollections of Holmes Rolston's wife Jane over the decades of her life married to a philosophical "thinker."
circa 2000.
Keywords: Rolston, Holmes, 1932-2025